UPAYA DIVERSIFIKASI KONSUMSI UBI JALAR DAN UBI KAYU SEBAGAI SUMBER KARBOHIDRAT - Eny Hari Widowati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
The diversify of food as source of protein,vitamin and mineral have succeeded to be conducted, but diversified of food as source of carbohydrate is still difficult to execute. Carbohydrate represent primary food which consumed by Central Java people. The source of carbohydrate which consumed by many people is rice, with consumption in the year 2005 equal to 52,18% while consumption all kinds of tubers only equal to 2,78% from goals which ought to 6%. Sweet potato and cassava represent the source of high energy. The aim of the research was to know consumption source of carbohydrate besides rice as part of effort to diversify consumtion of source of carbohudrate. Survay method was used in this research, in Wonogiri, Pati, Temanggung, and Semarang during 8 months, commencing from March 2006. Sample units was taken by Purposive stratified quota sampling method, consist of 25 farmers. Data was collected from primary and secondary data. Analysis for potency with availibility of consumption storey; level food, for the participant of, motif, frequency, target and consumtion produce by household measured with percentage. The highest potency of cassava avaibility during 5 year is in Wonogiri regency: 2,579.98 calorie/kap/day, sweet potato is in Semarang Regency :28,52 calorie/kap/day. The highest participation consumtion of cassava is in Semarang Regency, whereas the lowest participation consumption of sweet potato is in Wonogiri Regency and Semarang Regency. Frequency counted 2 times/month as a mean to consume it self equals to 30% Wonogiri Regency. The average consumption participation of sweet potato and cassava as diversification of carbohidrate consumptin is very high with motif as interval food with frequency 2 times/month. Diversified food as a mixer of primary food there are in Wonogiri Regency and Semarang Regency.